Increasing Economic Value for Farmers Through Improvements in Beef Cattle Business - Rusdiana, S; Talib, Chalid; Ishak, Andi B Lompengeng; Ferasyi, Teuku Reza (The International Journal of Tropical Veterinary and Biomedical Research, 2025)
Background and Aim: The study was conducted in Pabentengang Village, Bajeng District, Gowa Regency, South Sulawesi 2020.Materials and Methods: The study used a survey method of 25 farmers, using questionnaires and interviews. The research location is agricultural land and the community's main business is agriculture and beef cattle. Primary data and secondary data were analyzed descriptively, quantitatively, and economically. The purpose of this paper is to determine the increase in the economic value for farmers through improving beef cattle business.Results: The results showed that the profit of farmers by "paro" or profit sharing was IDR. 4,262,500/farmer/year, and the R/C value was 1.3. The profit of farmers from fattening is IDR. 9,847,000/farmer/period with an R/C value of 1.2. The profit of farmers by producing calves through AI with Limousin semen is IDR. 7,250,000/farmer/year, the R/C value is 1.9. Government support and policies are needed regarding economic feasibility for the welfare of farmers, so that the sustainability of the beef cattle business can be maintained. The strategies that need to be implemented are not only related to the technical aspects of animal husbandry, but also the institutional and communication aspects that are needed in a mutually sustainable manner.Conclusion: Beef cattle business by paro or with profit sharing, producing calves through AI and fattening, is economically feasible to be re-cultivated.